OPTIMASI PERSEDIAAN IKAN BANDENG TANPA DURI MENGGUNAKAN METODE STRATEGI EFISIENSI DALAM PRODUKSI - NURUL HIDAYAT; putrijuwita; Geo Feneri; Putri Nabila Marsha (Akademika : Jurnal Manajemen, Akuntansi, dan Bisnis., 2025)
Haji Dinare's Thornless Milkfish Production House is a small industry or home industry in Tarakan City that buys, processes, and markets processed milkfish products abroad. The recording process is still manual, in this Milkfish Production House still uses book records so that the data generated is less accurate, effective, and efficient. In addition, this milkfish production house has weaknesses that need to be improved, namely purchase and inventory reporting whose accuracy, effectiveness, and efficiency have not been met. The home industry that we raise, for example, the Production House of Thornless Milkfish, will be very good if it has a good management system so as to produce a total inventory cost that is close to optimal. One method to manage inventory properly is the Economic Order Quanit (EOQ) method, JIT, data collection, inventory turnover (Inventory Turnover Ratio), average inventory (Avarage Inventory), annual holding cost (Annual Holding Cost), and total annual inventory cost (Total Annual Inventory Cost).